THE CORRELATION OF THE RATE RELATION OF THE WAIST AND HIP (IRCQ) AND THE RATE OF THE BODY MASS (IMC) IN SCHZOFRENICS PATIENTS INSTITUTIONALIZED (Fiep Bulletin - online, 2013)
The schizophrenia has its main characteristics, the presence of peculiar psychotic symptoms in the active phase of the illness and functioning below the highest level previously reached (AMERICAN PSYCHRIATRIC ASSOCIATION, 2002). Objective: The present article has as objective correlate the rate of waist-hip relation and the rate of the body mass (ICM) in a group of schizophrenics institutionalized people. Methodology: Forty-nine male schizophrenic patients, that were chosen, according to the diagnostic of Schizophrenia (DSM IV), with average of 40, 35years old, were submitted to a physics evaluation to calculate the IMC, the weight divided for the height twice, the other one of IRCQ, that is the circumference of the waist and then was done the correlation of two tests using Descriptive Statistics (SPSS, 13.0). Results: The most relevant alterations were found on the 46% of the sample that shows a Very High Risk, Just one person with acceptable weight, 8 with weight in excess of level 1.12 with excess of weight level 2 and 1 person with excess of weight level 3. Checking the relation to the rate of the relation of waist and hip, the investigated people showed average of 0.9347, which corresponds to the Moderated Classification, that when related to the rate of Body Mass, checked that the average of this investigated group was of 27.36, being considered Light obesity (World Health Organization). Conclusion: With the elaboration of this research, it was evidenced that there was an important relation between the IRCQ and IMC, because the patients showed an average IRCQ with moderated risk, in its majority showed an excess of weight too.
Keywords: Schizophrenia; Rate of waist-hip relation; Rate of Body Mass